Effect of Water Stress on the Physiological Characteristics of Five Basil (Ocimum basilicum L.) Cultivars - Iakovos Kalamartzis; George Menexes; Pantazis Georgiou; Christos Dordas (Agronomy, 2020)
Water stress in one of the most important abiotic stresses that affects the productivity of many crop species worldwide. In addition, the climate change creates new challenges for crop adaptation especially as water resources become limited and the increase in water stress becomes more pronounced even in areas where there is adequate water supply. The objective of the present study was to determine the effect of water stress on physiological characteristics of five cultivars of basil under field conditions. Water stress affected leaf temperature, dry herb yield, leaf water potential, assimilation rate and gas exchange parameters, quantum yield, instantaneous water use efficiency (WUE), and essential oil content. From the physiological characteristics water potential and assimilation rate can be used for the selection of basil cultivars tolerant to water stress. In addition, essential oil content was lower under water stress indicating that essential oil content is correlated with water availability. From the present study it is obvious that there are tolerant basil cultivars to water stress and can be found using physiological traits such as water potential and assimilation rate and can be used to save and use water more sustainable and also conserve the water resources.